The HD-ZIP IV transcription factor GL2-LIKE regulates male flowering time and fertility in cucumber. (3rd June 2020) - Cai, Yanling; Bartholomew, Ezra S; Dong, Mingming; Zhai, Xuling; Yin, Shuai; Zhang, Yaqi; Feng, Zhongxuan; Wu, Licai; Liu, Wan; Shan, Nan; Zhang, Xiao; Ren, Huazhong; et al.
Abstract : CsGL2-LIKE, a HD-ZIP IV transcription factor, regulates male flowering time and fertility in cucumber and interacts with the jasmonate repressor CsJAZ1 to form a HD-ZIP IV–CsJAZ1 complex. Abstract: Cucumber is dioecious by nature, having both male and female flowers, and is a model system for unisexual flower development. Knowledge related to male flowering is limited, but it is reported to be regulated by transcription factors and hormone signals. Here, we report functional characterization of the cucumber ( Cucumis sativus ) GL2-LIKE gene, which encodes a homeodomain leucine zipper (HD-ZIP) IV transcription factor that plays an important role in regulating male flower development. Spatial–temporal expression analyses revealed high-level expression of CsGL2-LIKE in the male flower buds and anthers. CsGL2-LIKE is closely related to AtGL2, which is known to play a key role in trichome development. However, ectopic expression of CsGL2-LIKE in Arabidopsis gl2-8 mutant was unable to rescue the gl2-8 phenotype. Interestingly, the silencing of CsGL2-LIKE delayed male flowering by inhibiting the expression of the florigen gene FT and reduced pollen vigor and seed viability. Protein–protein interaction assays showed that CsGL2-LIKE interacts with the jasmonate ZIM domain protein CsJAZ1 to form a HD-ZIP IV–CsJAZ1 complex. Collectively, our study indicates that CsGL2-LIKE regulates male flowering in cucumber, and reveals a novel function of a HD-ZIP IV transcription factor in regulating male flower development of cucumber.